ANTIFUNGAL EFFICIENCY OF COPPER OXYCHLORIDE-CONJUGATED SILVER NANOPARTICLES AGAINST COLLETOTRICHUM GLOEOSPORIOIDES WHICH CAUSES ANTHRACNOSE DISEASE - RAGHAVENDRA SN; RAGHU HS; DIVYASHREE K; RAJESHWARA AN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Anthracnose disease is caused by Colletotrichum gloeosporioides, affecting most of the fruit and vegetable plants. The present study is aimed to synthesize silver nanoparticles (AgNPs) using neem extract and conjugate then with fungicide to check the antifungal activity against anthracnose disease. Methods: In the current study, we have synthesized copper oxychloride-conjugated AgNPs (COC-AgNPs) by a biological method using neem extract and have tested their effectiveness against C. gloeosporioides. The COC-AgNPs were characterized by UV–visible spectroscopy, fourier-transform infrared, scanning electron microscopy, and X-ray diffraction analysis, and in vitro antifungal activity was investigated. Results: The shape of COC-AgNPs was found to be spherical with an average particle size of 21–25 nm. The fungicide-conjugated AgNPs exhibited highest growth inhibition of C. gloeosporioides (~187%) as compared to fungicide copper oxychloride. Conclusion: These results indicate that the COC-AgNPs could be effectively used to control anthracnose disease in mango and in other crops. These COC-AgNPs can drastically reduce the amount of fungicide currently used which will reduce the environmental pollution caused by the fungicide.